Dinamika Kehidupan Beragama di Kampung Madras - Khairina; Meyniar Albina (CV. ITTC INDONESIA, 2024)
This study examines the dynamics of religious life in Kampung Madras, Medan, which is known as a symbol of tolerance and harmony between religious communities amidst ethnic, cultural, and religious diversity. This village is a real example of harmonious pluralism, demonstrated by the existence of houses of worship from various religions side by side, such as mosques, churches, temples, and gurdwaras. This study uses a descriptive qualitative method with a phenomenological approach, aiming to understand the phenomenon of tolerance from the perspective of the local community's experience. The results of the study show that harmony in Kampung Madras is supported by a collective awareness of the importance of respecting differences, interfaith marriage relationships, and strong kinship ties. The practice of religious moderation is seen through interfaith participation in various religious celebrations. Conflicts rarely occur, and if there are, they are resolved through direct communication that prioritizes local wisdom. However, this tolerance still has limits, especially in terms of faith, which is maintained as a fundamental principle. This study confirms that tolerance in Kampung Madras is not a form of religious relativism, but rather an effort to maintain social harmony without sacrificing each person's basic beliefs. Madras Village provides an example of how multicultural societies can live side by side peacefully through dialogue, understanding, and solidarity.